Stability of Woven Frames - Li, Xue-Bin; Zhu, Yu-Can (Frontiers in Physics, 2022)
This paper studies the stability of woven frames by introducing some special limits. We show that there exist certain relations among the different types of convergence of frames, and obtain some new and more general stability results. As an application of these results, we provide a method for constructing woven frames.